The Personality Traits and P300 of Offspring of Parents With Alcohol Dependence Differ Depending on Current Risky Drinking: A Preliminary Case-Control Study - Qiu, Yujia; Wang, Jing; Zhang, Ying; Wu, Tingfang; Li, Bing; Yu, Xin (Frontiers in Psychiatry, 2022)
Aims: The aim of this study was to investigate the personality traits, and P300 component in the offspring of parents with alcohol dependence (OPAD) currently engaged in risky drinking and those not engaged in risky drinking, and to further explore the correlates of problematic alcohol use. Methods: A case-control study was conducted according to the cutoff of the Alcohol Use Disorder Identification Test (AUDIT). The frequency of the TaqIA polymorphism of the dopamine receptor D2 gene associated with alcohol dependence was compared between the two OPAD groups. Tridimensional Personality Questionnaire (TPQ), The Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST), and the MINI-International Neuropsychiatric Interview (M.I.N.I.) were measured or interviewed in OPAD not engaged in risky drinking(resilient) (n=35) and those currently engaged in risky drinking(vulnerable)(n=20). P300 was measured to test the possible electrophysiological differences. The correlates of alcohol use were analyzed. Results: Vulnerable OPAD showed higher novelty seeking subscale scores (NS4) (4.45±2.012 vs. 3.31±1.728, p<0.05) and harm avoidance subscale scores (HA4) (5.3±2.319 vs. 3.66±2.461, p<0.05) than resilient OPAD, while the total scores of each dimension showed no significant difference. OPAD engaged in risky drinking showed more tobacco use than OPAD resistant to risky drinking. OPAD with risky drinking showed a shorter P300 latency than resilient OPAD on Fz electrodes. AUDIT scores of OPAD were correlated with P300 latency. Conclusions: P300 differed between OPAD with and without risky drinking and alcohol use was associated with P300 latency, indicating that P300 may be used in the early detection of vulnerable OPAD and early intervention in the future.